Low-temperature studies of Cr3+ ions in natural and neutron-irradiated Mg-Al spinel - Mironova-Ulmane, Nina; Popov, Anatoli I.; Krieke, Guna; Antuzevics, Andris; Skvortsova, V.; Elsts, Edgars; Sarakovskis, Anatolijs (American Institute of Physics, 2020)
Original results on the EPR and photoluminescence Cr3+ ions in natural magnesium aluminum spinel (MgAl2O4) are presented. The photoluminescence spectra of Cr3+ ions in natural MgAl2O4 have been measured before and after irradiated by fast neutrons.---- / / / ---- This is the preprint version of the following article: N. Mironova-Ulmane, A. I. Popov, G. Krieke, A. Antuzevics, V. Skvortsova, E. Elsts, and A. Sarakovskis, Low-temperature studies of Cr3+ ions in natural and neutron-irradiated Mg-Al spinel, Low Temperature Physics,46, 1154 (2020), DOI https://doi.org/10.1063/10.0002467, which has been published in final form at https://aip.scitation.org/doi/10.1063/10.0002467. This article may be used for non-commercial purposes in accordance with American Institute of Physics terms and conditions for Sharing and Self-Archiving.
This study was supported by a grant from Latvian Council of Science (agreement No. LZP-2018/1-0214).
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; photoluminescence spectra; MgAl2O4; fast neutrons